The Dilemma of the Practice of Water Privatization in the Era of the ASEAN Global Community - Suteki, Suteki (Law Research Review Quarterly, 2015)
The facts show that the fulfillment of the rights to water for some of the world's population, including Indonesia, has not yet been achieved. This fact encourages efforts to meet water levels to be included as one of the Millennium Development Goals (MDGS) goals as the 10th tarhet. The target is set to reduce by half of the world's population who do not have access to clean water and sanitation by 2015.